Microstructural and electrical properties of Pb(Zr0.52Ti0.48)O-3 films grown on p-InSb (111) substrates at low temperature - Kim, TW; Yoon, YS (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
Ferroelectric Pb(Zr0.52Ti0.18)O-3 thin films were grown on p-InSb (111) substrates by using a radio-frequency magnetron sputtering method at low temperature ( similar to 350 degrees C). Atomic force microscopy (AFM) and X-ray diffraction (XRD) measurements showed that the Pb(Zr0.52Ti0.48)O-3 film layers gown on InSb substrates were polycrystalline thin films with smooth surfaces, and Auger electron spectroscopy (AES) measurements indicated that the compositions of the as-grown films consisted of lead, zirconium, titanium and oxygen. Transmission electron microscopy (TEM) and selected-area electron diffraction measurements showed that the grown Pb(Zr0.52Ti0.48)O-3 was a polycrystalline layer with small domains and that the Pb(Zr0.52Ti0.48)O-3/InSb (111) heterointerface had no significant interface problems. Room-temperature current-voltage and capacitance-voltage (C-V) measurements clearly revealed a metal-insulator-semiconductor behavior for the Pb(Zr0.52Ti0.48)O-3 insulator gates, and the interface state densities at the Pb(Zr0.52Ti0.48)O-3/p-InSb interfaces, as determined from the C-V measurements, were approximately high 10(11) eV(-1) cm(-2) at the middle of the InSb energy gap. The dielectric constant of the Pb(Zr0.52Ti0.48)O-3 thin film, as determined from the C-V measurements, was as large as 803.2. These results indicate that the Pb(Zr0.52Ti0.48)O-3 layers grown on p-InSb (111) substrates at low temperatures can be used both for high-density dynamic memories and highspeed varistors based on InSb substrates. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: CHEMICAL-VAPOR-DEPOSITION; BATIO3 THIN-FILMS; EPITAXIAL-GROWTH